Psychogenic dysphonia: diversity of clinical and vocal manifestations in a case series - Garcia Martins, Regina Helena [UNESP]; Mendes Tavares, Elaine Lara [UNESP]; Ranalli, Paula Ferreira [UNESP]; Branco, Anete [UNESP]; Benito Pessin, Adriana Bueno [UNESP] (Assoc Brasileira Otorrinolaringologia e cirurgia Cervicofacial, 2014)
Introduction: Psychogenic dysphonia is a functional disorder with variable clinical manifestations.Objective: To assess the clinical and vocal characteristics of patients with psychogenic dysphonia in a case series.Methods: The study included 28 adult patients with psychogenic dysphonia, evaluated at a University hospital in the last ten years. Assessed variables included gender, age, occupation, vocal symptoms, vocal characteristics, and videolaryngostroboscopic findings.Results: 28 patients (26 women and 2 men) were assessed. Their occupations included: housekeeper (n = 17), teacher (n = 4), salesclerk (n = 4), nurse (n = 1), retired (n = 1), and psychologist (n = 1). Sudden symptom onset was reported by 16 patients and progressive symptom onset was reported by 12; intermittent evolution was reported by 15; symptom duration longer than three months was reported by 21 patients. Videolaryngostroboscopy showed only functional disorders; no patient had structural lesions or changes in vocal fold mobility. Conversion aphonia, skeletal muscle tension, and intermittent voicing were the most frequent vocal emission manifestation forms.Conclusions: In this case series of patients with psychogenic dysphonia, the most frequent form of clinical presentation was conversion aphonia, followed by musculoskeletal tension and intermittent voicing. The clinical and vocal aspects of 28 patients with psychogenic dysphonia, as well as the particularities of each case, are discussed. (C) 2014 Associacao Brasileira de Otorrinolaringologia e Cirurgia Cervico-Facial. Published by Elsevier Editora Ltda. All rights reserved.
Keywords: Voice disorders; Clinical psychology; Psychopathology; Psychotherapy